2006
DOI: 10.1111/j.1445-6664.2006.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aryl acylamidase activity from propanil‐resistant barnyardgrass (Echinochloa crus‐galli [L.] Beauv.)

Abstract: The enzyme, aryl acylamidase, was characterized in propanil-susceptible and propanil-resistant barnyardgrass with respect to kinetic parameters, the effects of inhibitors, and the levels of activity in dark-and light-grown tissues. The enzyme reaction in the resistant tissue preparation proceeded linearly with time over a 5 h time course, while activity in the susceptible tissue preparation was 2-to 4-fold lower and the activity tended to decrease after 2 h. The apparent K m values were 62.1 mmol L −1 and 3.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…When Echinochloa spp. evolved resistance to propanil, it was less of a surprise that it had upregulated an arylamidase similar to that of rice 19, 20…”
Section: Herbicide Selectivity—a Predictor Of Resistance Mechanisms?mentioning
confidence: 99%
“…When Echinochloa spp. evolved resistance to propanil, it was less of a surprise that it had upregulated an arylamidase similar to that of rice 19, 20…”
Section: Herbicide Selectivity—a Predictor Of Resistance Mechanisms?mentioning
confidence: 99%
“…An arylacyl amidase active toward the herbicide propanil has been described in rice and competing weeds (Leah et al 1994). The enzyme responsible has yet to be characterized, though a mitochondrial protein appears to be the most likely candidate for catalyzing this unusual activity (Hirase and Hoagland 2006). In addition other hydrolytic processes can give rise to xenobiotic detoxification.…”
Section: Phase 1 Enzymes -Hydrolasesmentioning
confidence: 99%
“…However, metabolism studies on the R‐BYG biotype showed that elevated metabolism was responsible for propanil resistance (Carey et al . 1997) and, later, enzyme‐isolation and characterization studies, using the R‐BYG and S‐BYG biotypes, substantiated the metabolic resistance mechanism in the R‐BYG biotype (Hirase & Hoagland 2006). Similar results were obtained for the R‐JR biotype (Martinez et al .…”
mentioning
confidence: 93%